Pengaruh Electronic Word of Mouth dan Brand Image terhadap Purchase Decision Pada Aplikasi Fore Coffee di Kota Bandung - Ade Santika; R Oktini, Dede; Dwi Nugraha, Yudha (UNISBA Press, 2024)
Abstract. This study aims to test and find out (1) how is the description of Electronic word of mouth and Brand image on Purchase decision for Fore Coffee application users in Bandung City? (2) How does Electronic word of mouth affect Purchase decision for Fore Coffee application users in Bandung City? (3) How does Brand image affect Purchase decision for Fore Coffee application users in Bandung City? (4) How does Electronic word of mouth and Brand image affect Purchase decision for Fore Coffee application users in Bandung City. This research is included in the type of descriptive and verification research with quantitative methods. The sampling technique used is nonprobability sampling, namely Purposive sampling. The population in this study are consumers who use the Fore Coffee application who live in Bandung and have made transactions or purchases through the Fore Coffee application in the last 6 months or 1 year with a total of 95 respondents. The data analysis used is multiple linear regression analysis with hypothesis testing using, T test, F test, and coefficient of determination. The results of this study indicate that electronic word of mouth partially affects the purchase decision, and brand image affects the purchase decision. Then simultaneously Electronic word of mouth and Brand image have a significant effect on Purchase decision on the Fore Coffee application in Bandung City. Abstrak. Penelitian ini bertujuan untuk menguji dan mengetahui (1) bagaimana gambaran Electronic word of mouth dan Brand image terhadap Purchase decision pada pengguna aplikasi Fore Coffee di Kota Bandung? (2) Bagaimana pengaruh Electronic word of mouth terhadap Purchase decision pada pengguna aplikasi Fore Coffee di Kota Bandung? (3) Bagaimana pengaruh Brand image terhadap Purchase decision pada pengguna aplikasi Fore Coffee di Kota Bandung? (4) Bagaimana pengaruh Electronic word of mouth dan Brand image terhadap Purchase decision pada pengguna aplikasi Fore Coffee di Kota Bandung?. Penelitian ini termasuk ke dalam jenis penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobability sampling yaitu Purposive sampling. Populasi dalam penelitian ini adalah konsumen pengguna aplikasi Fore Coffee yang berdomisili di Kota Bandung dan pernah melakukan transaksi atau pembelian melalui aplikasi Fore Coffee dalam 6 bulan atau 1 tahun terakhir dengan jumlah 95 responden. Analisis data yang digunakan adalah analisis regresi linier berganda dengan pengujian hipotesis menggunakan, uji T, uji F, dan koefisien determinasi. Hasil penelitian ini menunjukkan Electronic word of mouth secara parsial berpengaruh terhadap Purchase decision, dan Brand image berpengaruh terhadap Purchase decision. Lalu secara simultan Electronic word of mouth dan Brand image berpengaruh signifikan terhadap Purchase decision pada aplikasi Fore Coffee di Kota Bandung.